The battle of the Zé Gotinhas: The schismogenesis of images and political audiences on Brazilian social media - Kelly Cristiane da Silva; Fábio de Oliveira Martins (Vibrant: Virtual Brazilian Anthropology)
Abstract: Centring on a dispute between different versions of an icon of public health and immunization policies in Brazil, we explore the analytic potential of the rival images and their embedding in a dynamic structure of long-term schismogenesis fed by former president Jair Bolsonaro, his political allies and publics. The conflict over different versions of Zé Gotinha published at the beginning of Covid-19 vaccination - one produced by the illustrator and designer-activist Cristiano Siqueira, another commissioned by Eduardo Bolsonaro, a federal deputy and a son of the former president-inserted in the context of a semiological guerrilla war, allows us to examine the different images as, simultaneously, part of a confrontation that begins with the images and ends in the structural forces perpetuating the schismogenesis between allies of the former president and his adversaries. Over the course of the text, we identify symbolic offensives and retreats in accordance with the political situation of the moment.